A fotografia como arte moderna : o estilo documentário de Walker Evans em American Photographs - Oliveira, Cleriston Boechat de (2013)
This dissertation investigates the “documentary style” of American photographer Walker Evans in the exhibition and in the book American Photographs, 1938. It analyzes the author’s photographs by approaching critical texts by various authors, including Wal